2024
DOI: 10.29333/iji.2024.17135a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mobile-based Interactive Multimedia on Thinking Engagement and Cooperation

Maroua Rogti

Abstract: Recent studies show limited research in the Algerian context on the development of learning multimedia that effectively addresses 21st century skills such as critical thinking, communication, cooperation, and creativity. However, with the continuous growth of digital multimedia and information technologies, there is an urge for utilizing 21st century skills and interacting with others through interactive multimedia tools. This study aims to investigate the effect of mobile-based interactive multimedia on devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…This framework emphasizes the importance of learner engagement and autonomous learning ability in the context of mobile learning (Ward et al, 2024). Several studies have explored the relationship between technology use, self-directed learning, and learner engagement (Rogti, 2024). For example, research has shown that technology and social media can enhance self-directed learning skills and student engagement (Wiboolyasarin & Jinowat, 2024).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This framework emphasizes the importance of learner engagement and autonomous learning ability in the context of mobile learning (Ward et al, 2024). Several studies have explored the relationship between technology use, self-directed learning, and learner engagement (Rogti, 2024). For example, research has shown that technology and social media can enhance self-directed learning skills and student engagement (Wiboolyasarin & Jinowat, 2024).…”
Section: Literature Reviewmentioning
confidence: 99%